Tricuspid Valve Dysplasia in a Dog - de Carvalho Cid, Gabriela; Alonso, Luciano da Silva; de Castro Pires, Ana Paula; Gonçalves, Mariana Siqueira d'Avila Taïna; Gonçalves, Taïna; Carvalho, Nathália da Silva; Nogueira, Vivian de Assunção; França, Ticiana Nascimento (Acta Scientiae Veterinariae, 2019)
Background: Congenital cardiac diseases are a common cause of death in puppies. Tricuspid valve dysplasia is characterized by thickening and displacement of the leaflets of the tricuspid valve, agenesis of the valves, and incomplete separation of valve components. Papillary muscles may fuse and display shortened or absent chordae tendineae that contribute to tricuspid regurgitation. Diagnostic features of tricuspid valve dysplasia include cardiomegaly with massive right atrium enlargement on thoracic radiography and tricuspid insufficiency on an ultrasound. We aimed to describe clinicopathological findings in a dog (Canis familiaris) with tricuspid dysplasia. Case: We aimed to describe tricuspid valve dysplasia in a dog referred for necropsy at the Anatomical Pathology Sector of The Rural Federal University of Rio de Janeiro, Brazil, with a clinical history of abdominal swelling, dyspnea, cyanosis, ascites, and prostration. Echocardiography and abdominal ultrasound revealed right ventricular enlargement, hepatomegaly, and splenomegaly. Examination of the heart showed prominent enlargement, thickening and dilation of the right chambers, thickening of the tricuspid leaflets, and moderately shortened chordae tendineae. The liver was enlarged, with a nutmeg pattern, and foci of clotting and fibrin adhesions in the lateral right lobule. Discussion: Epidemiological, clinical, and pathological findings were consistent with tricuspid valve dysplasia. Although structural abnormalities of the tricuspid and mitral valves are well known in fetuses and neonates, congenital and secondary tricuspid malformations are rare in dogs. The survival rate is associated with the severity of heart lesions. Tricuspid valve dysplasia is mostly observed in large-breed dogs (>20 kg), particularly in Labrador Retrievers, Boxers, and German Shepherds. Regardless, most dogs with tricuspid valve dysplasia are of a pure-breed, which differs from our findings because our dog was a mongrel. Our dog displayed signs of dyspnea, cyanosis, abdominal swelling, prostration, and enlarged liver and spleen on ultrasound examination. Tricuspid valve dysplasia led to heart enlargement and right congestive heart failure, with consequent ascites, abdominal swelling, weakness, lethargy, jugular venous distension, and hepatomegaly. Overall, the heart showed prominent enlargement, thickening and dilation of the right chambers, thickening of the tricuspid leaflets, and moderately shortened chordae tendineae. The liver had a nutmeg pattern. Tricuspid valve dysplasia is characterized by malformation of the tricuspid valve leaflets, chord tendineae, or papillary muscles. Malformed tricuspid valves are known to result in variable degrees of regurgitation, leading to right atrial overflow and ventricular eccentric hypertrophy. Differential diagnosis includes myocarditis, tricuspid valve endocarditis, tricuspid endocardiosis, tricuspid valve prolapse and right ventricular dysplasia, right ventricular enlargement with tricuspidal regurgitation due to pulmonary insufficiency, and arrhythmogenic right ventricular cardiomyopathy. Signs of heart murmurs (irregular sounds of the heart) on clinical examination may indicate an irregular blood flow pattern, and imaging tests may be necessary for assessing the presence and severity of any lesions. The epidemiologic, clinical, and pathological findings were consistent with those of tricuspid valve dysplasia.